Google Classroom Acceptance Level of High School Students Using the Technology Acceptance Model - Tateng Gunadi; Widyo Nugroho (Dinasti Publisher, 2023)
Learning activities in all Indonesian schools have been suspended since the Covid-19 pandemic occurred in early April 2020. Google Classroom as a popular and widely used application plays an important role in the distance learning process. However, it is not yet known to what extent the acceptance of these applications for users. The purpose of this study was to analyze the level of acceptance of the Google Classroom application through the Technology Acceptance Model for state high school students in Bogor City. This study uses quantitative methods through surveys that are analyzed descriptive statistics. The results showed that the level of acceptance of Google Classroom among state high school students in Bogor City was high. Almost all of the problem formulations can be responded to properly and six of the seven hypotheses can be proven by the existence of a positive influence on the relationship between variables. This research can be a reference for decision makers in high school level schools that the Google Classroom application can be used as a Learning Management System in distance learning during the Covid-19 pandemic, other conditions that do not allow direct learning, and blended learning.